Predictors of early childhood HIV testing among children of sex workers living with HIV in Cameroon - Amrita Rao; Sheree Schwartz; Serge C. Billong; Anna Bowring; Ghislaine Fouda; Flavien Ndonko; Iliassou Njindam; Daniel Levitt; Anne-C. Bissek; Oudou Njoya; Stefan Baral (BMC, 2019)
Abstract Background Despite recent progress, there exist gaps in the prevention of vertical HIV transmission program access and uptake in Cameroon. Female sex workers (FSW), many of whom are mothers, are disproportionately affected by HIV and have specific barriers to HIV testing and treatment access. Testing for HIV-exposed infants is crucial in monitoring for incident infection and timely intervention. This study explores the level of early childhood testing and also associations between antenatal care (ANC) attendance and other factors and early childhood HIV testing among FSW in Cameroon. Methods FSW were recruited to participate in an integrated biobehavioral survey in Cameroon between December 2015 and October 2016. Women were included in these analyses if they were living with HIV and had at least one living child. Both univariate and multivariable logistic regression were used to look at predictors of a child being tested for HIV before age five. Results A total of 481/2255 FSW were eligible for these analyses as they were HIV seropositive and had at least one living child at the time of the study. Women included in these analyses had a median age of 35(IQR 30-41). Nearly 70% reported none of their children had been tested for HIV before age five (326/481), and 3.5%(17/481) reported one or more of their children had been diagnosed with HIV. ANC attendance (adjusted OR 2.12, 95% CI: [1.02, 4.55]), awareness of HIV status (aOR 3.70[2.30, 5.93]), pregnancy intentions (aOR 1.89[1.16, 3.08]), and higher education (aOR 2.17[1.01, 4.71]) were all independently associated with increased odds of women having a greater proportion of children tested for HIV before age five. Regional differences in early childhood testing were also observed. Conclusion Vertical transmission of HIV remains a challenge in Cameroon, and HIV testing among children of FSW living with HIV was very low. ANC attendance and promotion of the mother's health were associated with increased child HIV testing. For women at high risk of HIV and for whom engagement in the health system is low, strategies to promote and ensure ANC attendance are essential for their health and the health of their children.